Pop-porn : pornography in American culture - Hall, Ann C., 1959-; Bishop, Mardia J., 1963- (Westport, Conn. : Praeger, 2007)
"There is a new wave of pornographic entertainment in contemporary American culture; liberated from X-rated bookstores and strip clubs, porn is everywhere. Pop-Porn seeks to examine this phenomenon in some of its most striking manifestations. Written from a variety of perspectives and on a variety of topics representing the widespread increase of soft-core porn in our culture, Pop-Porn offers a detailed and complex approach to the porn industry in America." "Rather than focusing on the current polarity of basic pro and con views on this topic - a polarity that ultimately hinders discussion - these essays show that pornographic content is subtly and profoundly embedded in our culture fabric."--Jacket.
Pushing the envelope : the role of the mass media in the mainstreaming of pornography / Katherine N. Kinnick -- Panda porn, children, Google, and other fantasies / Judith Roof -- The making of a pre-pubescent porn star : contemporary fashion for elementary school girls / Mardia J. Bishop -- Hot bodies on campus : the performance of porn chic / Hanna B. Harvey and Karen Robinson -- One night in Paris (Hilton) : wealth, celebrity, and the politics of humiliation / Thomas Fahy -- Fear factor : pornography, reality television, and red state America / Jesse Kavadlo -- Freak shows in Jesus land : Howard Stern in George Bush's America / Ann C. Hall -- Toys are us : feminisms and the consumption of sexuality / Dawn Heinecken -- Clean porn : the visual aesthetics of hygiene, hot sex, and hair removal / Susann Cokal -- Your privacy's showing : pornography at your local library / Sue Banks.
Includes bibliographical references (pages 165-192) and index.
Keywords: Pornography -- United States; Sex in mass media; Pornography; Sex in mass media; United States; Massenmedien; Pornographie; USA; Pornografi; Sex i massmedia